In vivo measurement of afferent activity with axon-specific calcium imaging. (September 2018) - Broussard, Gerard; Liang, Yajie; Fridman, Marina; Unger, Elizabeth; Meng, Guanghan; Xiao, Xian; Ji, Na; Petreanu, Leopoldo; Tian, Lin
Abstract In vivo calcium imaging from axons provides direct interrogation of afferent neural activity, informing the neural representations that a local circuit receives. Unlike in somata and dendrites, axonal recording of neural activity—both electrically and optically—has been difficult to achieve, thus preventing comprehensive understanding of neuronal circuit function. Here we developed an active transportation strategy to enrich GCaMP6, a genetically encoded calcium indicator, uniformly in axons with sufficient brightness, signal-to-noise ratio, and photostability to allow robust, structure-specific imaging of presynaptic activity in awake mice. Axon-targeted GCaMP6 enables frame-to-frame correlation for motion correction in axons and permits subcellular-resolution recording of axonal activity in previously inaccessible deep-brain areas. We used axon-targeted GCaMP6 to record layer-specific local afferents without contamination from somata or from intermingled dendrites in the cortex. We expect that axon-targeted GCaMP6 will facilitate new applications in investigating afferent signals relayed by genetically defined neuronal populations within and across specific brain regions. The authors introduce a variant GCaMP that is targeted to axons. Due to its strong brightness, signal-to-noise ratio, and photostability, this tool, named axon-GCaMP, enables robust Ca2+ imaging in individual axons, including in vivo in awake mice.